Efficiency, Net Interest Margin, and Loan to Deposit Ratio on Profitability of Nepalese Commercial Banks - Mahaseth, Ramesh Kumar (Nepalese Journal of Business, 2024)
This study examines the effect of capital adequacy ratio, non-performing loan, operational efficiency, net interest margin, and loan to deposit ratio on profitability of Nepalese commercial banks. Return on assets and earnings per share are the selected dependent variables. The selected independent variables are net interest margin, loan to deposit ratio, leverage, capital adequacy ratio, operating efficiency, and non-performing loans. The study is based on secondary data of 18 commercial banks with 126 observations for the study period from 2015/16 to 2021/22. The data were collected from Bank Supervision Report published by Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of capital adequacy ratio, non-performing loan, operational efficiency, net interest margin, and loan to deposit ratio on the profitability of Nepalese commercial banks. The study showed that non-performing loan has a negative impact on return on assets and earnings per share. It means that increase in non-performing loan leads to decrease in return on assets and earnings per share. In addition, loan-to-deposit ratio has a positive impact on return on assets. It indicates that increase in loan-to-deposit ratio leads to increase in return on assets. In contrast, loan-to-deposit ratio has a negative impact on earnings per share. It indicates that increase in loan-to-deposit ratio leads to decrease in earnings per share. Similarly, the study also showed that net interest margin has a positive impact on return on assets and earnings per share. It means that higher the net interest margin, higher would be the return on assets and earnings per share. Moreover, operating efficiency has a negative impact on return on assets and earnings per share. It shows that higher the operating efficiency, lower would be the return on assets and earnings per share. Furthermore, capital adequacy ratio has a positive impact on return on assets. It shows that higher the capital adequacy ratio, higher would be the return on assets.